2020
DOI: 10.1177/0959683619895577
|View full text |Cite
|
Sign up to set email alerts
|

Holocene climate variability and Indian Summer Monsoon: An overview

Abstract: The response of the Indian Summer Monsoon (ISM) to forcing factors and climate variables has not yet fully explored, even though the ISM plays a pivotal role in the socio-economics of the Indian subcontinent and nearby areas. The ISM progression over Indian landmass is a manifestation of the Intertropical Convergence Zone (ITCZ) migration over the northern Indian Ocean and the Indian subcontinent. The recent anomalous behaviour of ISM raises the need for a better understanding of its spatio-temporal changes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 316 publications
(612 reference statements)
2
30
0
Order By: Relevance
“…Signatures of changes in insolation are reflected in the changes of the northern hemisphere monsoon systems (Staubwasser et al, 2003). Past climate records based on proxy reconstructions from India and neighborhood surroundings of the Indian region (see the review by Dixit and Tandon, 2016;Banerji et al, 2020;Tejavath et al, 2020 for the details and references) report centennial to millennial-scale changes in the ISMR during the Holocene ( 12 kyr BP to present). These studies, in general, show that from the early Holocene period (9 kyr BP) to late Holocene (3 kyr BP), the ISMR shows a long-term decreasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…Signatures of changes in insolation are reflected in the changes of the northern hemisphere monsoon systems (Staubwasser et al, 2003). Past climate records based on proxy reconstructions from India and neighborhood surroundings of the Indian region (see the review by Dixit and Tandon, 2016;Banerji et al, 2020;Tejavath et al, 2020 for the details and references) report centennial to millennial-scale changes in the ISMR during the Holocene ( 12 kyr BP to present). These studies, in general, show that from the early Holocene period (9 kyr BP) to late Holocene (3 kyr BP), the ISMR shows a long-term decreasing trend.…”
Section: Introductionmentioning
confidence: 99%
“…The studies revealed that the climate over the Indian subcontinent was warm and wet during the MWP while a dry climate prevailed during LIA. However, the prevalence of cool and wet climates has been delineated form northern and central India, which was associated with the plausible strengthening of western disturbances due to southward migration of the Inter Tropical Convergence Zone (ITCZ; Banerji et al, 2020;Kotlia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…But dry conditions were demonstrated for the Mediterranean and the China/ Tibetan Plateau (Helama et al, 2017). In the Indian context, only a few studies have focussed on the climate of RWP and DACP (Banerji et al, 2015(Banerji et al, , 2017(Banerji et al, , 2019(Banerji et al, , 2020Misra et al, 2018;Naidu et al, 2020) of the first millennium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the influence of the mid-latitude westerlies shows a progressive decrease from the NW (Karakoram and Ladakh) to northeastern Himalaya (Benn and Owen, 1998). As far as the paleoclimatic/paleoenvironmental proxy record of the Higher Himalaya is concerned, the data are rudimentary, especially in relation to the sheer size of this sector; more specifically, the paleoclimatic data from the NW Himalaya are scarce (Ali et al, 2018; Bhushan et al, 2018; Banerji et al, 2020). In the case of the Higher Himalaya, focus must be given to the ISM, as it drives the majority of environmental and ecological changes in the region (Patnaik et al, 2012; Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%